2020
DOI: 10.1186/s43166-020-00039-w
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies spectrum in lupus nephritis in a cohort of Egyptian patients: relation to disease activity and prognostic value

Abstract: Background Specific autoantibodies are considered as an important marker in autoimmune rheumatic diseases and are of great value for the diagnosis and prognosis of systemic lupus erythematosus (SLE) patients. A total of eighteen autoantibodies were analyzed for their positivity in SLE patients and we evaluated the clinical relevance of the five most frequent autoantibodies: anti-dsDNA, anti-nucleosome, anti-histone, anti-Ro60, and anti-Ro52 on disease activity and renal affection in SLE Egyptian patients. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…Our findings suggested that the mean SLEDAI score increased with the increased number of autoantibodies positivity, and this was obvious in comparing the mean rank of SLEDAI of patients who are positive for two or three autoantibodies with those who are negative for all autoantibodies (p = 0.001) and also on comparing one positive with two positives, one positive with three positives and two positives with three positives (p = 0.016, p = 0.007, p = 0.001, respectively). This result is near to that of Elsayed and Mohafez, who found that when the autoantibodies positivity increased, the mean rank of SLEDAI increased [22].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Our findings suggested that the mean SLEDAI score increased with the increased number of autoantibodies positivity, and this was obvious in comparing the mean rank of SLEDAI of patients who are positive for two or three autoantibodies with those who are negative for all autoantibodies (p = 0.001) and also on comparing one positive with two positives, one positive with three positives and two positives with three positives (p = 0.016, p = 0.007, p = 0.001, respectively). This result is near to that of Elsayed and Mohafez, who found that when the autoantibodies positivity increased, the mean rank of SLEDAI increased [22].…”
Section: Discussionsupporting
confidence: 79%
“…Genetic variants of FC receptors were associated with susceptibility to SLE and with the disease severity [34]. Autoantibodies are essential biomarkers for autoimmune diseases, and they have important diagnostic and prognostic values in SLE [22]. Recently, there is a huge interest towards the use of ANA as a predictor for disease progression in SLE, aiming to decrease morbidity and mortality [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations